Little Fires Everywhere - Ng, Celeste (New York Penguin Press, 2017)
"Traces the intertwined fates of the picture-perfect Richardson family and the enigmatic mother and daughter who upend their lives"--
Keywords: Artists -- Fiction; Single mothers -- Fiction; Mothers and daughters -- Fiction; Landlord and tenant -- Fiction; Suburban life -- Fiction; Suburbs -- Fiction -- Ohio; Secrecy -- Fiction; Shaker Heights (Ohio) -- Fiction